2022
DOI: 10.3390/ijms23179855
|View full text |Cite
|
Sign up to set email alerts
|

Ionomic Combined with Transcriptomic and Metabolomic Analyses to Explore the Mechanism Underlying the Effect of Melatonin in Relieving Nutrient Stress in Apple

Abstract: Nutrient stress harms plant growth and yield. Melatonin is a biologically active, multifunctional hormone that relieves abiotic stress in plants. Although previous studies have shown that melatonin plays an important role in improving nutrient-use efficiency, the mechanism of its regulation of nutrient stress remains unclear. In this study, melatonin was applied to apple plants under nutrient stress, and morphological indices, physiological and biochemical indices, and stomatal morphology were evaluated. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…Our study found that MT treatment increased P and Cd uptake by oat seedlings, promoted root elongation and secondary root production, and improved root vigor, and this change in root morphology facilitated plant adaptation to stress. The same conclusion was reached in a study by Cao et al [62] on apples. In addition, appropriate concentrations of MT can improve the salt tolerance of plants through improving the transport of Na, Ca, and Mg ions by their leaves and roots and reconfiguring the ionic balance.…”
Section: Effect On Mineral Element Contentsupporting
confidence: 83%
“…Our study found that MT treatment increased P and Cd uptake by oat seedlings, promoted root elongation and secondary root production, and improved root vigor, and this change in root morphology facilitated plant adaptation to stress. The same conclusion was reached in a study by Cao et al [62] on apples. In addition, appropriate concentrations of MT can improve the salt tolerance of plants through improving the transport of Na, Ca, and Mg ions by their leaves and roots and reconfiguring the ionic balance.…”
Section: Effect On Mineral Element Contentsupporting
confidence: 83%
“…Transcriptomic analysis revealed that genes engaged in different metabolite pathways, signal transduction, transcription factors, and kinase activity were upregulated in response to stress. Genes involved in energy metabolism encoding mitochondrial ATPase, cytochrome c, ferredoxin, sucrose, and starch metabolism were identified in DEGs between melatonin-treated and untreated plants [63,64]. Earlier findings of Zhao et al [65] confirmed that applying melatonin increases the expression level of genes involved in signal transduction and carbon metabolism of plants under stress, thereby improving the photosynthetic process.…”
Section: Discussionmentioning
confidence: 79%
“…Genomic data aided with ionomics, particularly in combinations with forward and reverse genetic approaches, can detect cellular changes during abiotic stress conditions [ 265 ]. Recent reports showed that ionomics studies revealed the mechanisms of ion uptake under abiotic stresses in plants [ 266 , 267 , 268 ]. Moreover, transport, compartmentalization and exclusion of ions during adverse environmental conations were also monitored by ionomics.…”
Section: Proteogenomics Lipidomics Ionomics and Interactomicsmentioning
confidence: 99%
“…Moreover, transport, compartmentalization and exclusion of ions during adverse environmental conations were also monitored by ionomics. Although ionomics is a new field and there are only a few reports of ionomics studies under abiotic stress available, the trends are growing for ionomics studies [ 266 , 267 , 268 ]. In a general sense, ionomics are related to the ion content of an organism (here in plants) that is required for its growth and developmental processes under different environments and growth stages [ 269 ].…”
Section: Proteogenomics Lipidomics Ionomics and Interactomicsmentioning
confidence: 99%